2015
DOI: 10.1071/cp14241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defoliation by grazing or shoot removal on the root growth of field-grown wheat (Triticum aestivum L.)

Abstract: Dual-purpose crops for grazing and grain production can be highly profitable, provided grazing does not cause significant loss of grain yield. In many plants, defoliation causes a transient reduction in the allocation of resources to stem and root growth and remobilisation of soluble resources to re-establish leaf area rapidly. In Australia, the usual autumn and winter period of defoliation for grazed crops, May–July, coincides with a phase of near-linear root depth penetration in ungrazed crops, and the crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
6
20
0
Order By: Relevance
“…This is mostly the case in seasons where soil moisture is the limiting factor. However, in seasons with a full soil moisture profile, early sown crops explore more soil water owing to a deeper rooting system [14,15]. This is in agreement with the results of the field experiment of this study (Table 3), which was sown early (mid-March).…”
Section: Grain Yield and Harvest Indexsupporting
confidence: 88%
See 1 more Smart Citation
“…This is mostly the case in seasons where soil moisture is the limiting factor. However, in seasons with a full soil moisture profile, early sown crops explore more soil water owing to a deeper rooting system [14,15]. This is in agreement with the results of the field experiment of this study (Table 3), which was sown early (mid-March).…”
Section: Grain Yield and Harvest Indexsupporting
confidence: 88%
“…In seasons where there is sufficient soil moisture from an early start of the autumn rain, stored soil moisture from the fallow period or irrigation, early sown dual-purpose cereals into mild-warm soil and air temperatures offer a high dry matter quantity and quality [2]. Early sown crops develop a deeper rooting system to explore soil moisture and develop a high canopy, which increases radiation interception [14,15]. In Southern Australia, using the crop simulation model APSIM [16], Moore [17] found that establishment opportunities for winter cultivars, 15 mm or more of rain over a three-day period during April and May, occurred between 58% and 98% of the sites and years combinations considered.…”
Section: Introductionmentioning
confidence: 99%
“…Rasmussen et al (2015) found that soil N levels in spring were generally low, in the range of 1-5 kg N ha -1 per 10 cm soil layer, while others have found slightly higher values; for example, Beaudoin et al (2005) found levels between 5 and 10 kg N ha -1 . In both Denmark and Australia, the level of N available to wheat within deeper layers has been found to vary between 1 and 15 kg N ha -1 per 10 cm soil (Thorup- Kirkegaard et al, 2015). In the high soil N examples, between 100 and 200 kg of N or more per hectare is found in the sub-soil below 0Á50 m depth.…”
Section: The Availability Of Water and N Resources In The Sub-soilmentioning
confidence: 99%
“…Previous research has shown that root growth of canola ceases immediately after defoliation, and taproot starch reserves are remobilised to support new leaf area, leading to gradual loss of fine roots (McCormick et al 2012(McCormick et al , 2013. In testing whether similar effects occur in cereal crops, Kirkegaard et al (2015) conducted extensive field experiments and found little evidence that grazing influences root penetration or final rooting depth, except when defoliation occurs regularly and in early plant development. Their work supports earlier conclusions of Harrison et al (2011cHarrison et al ( , 2012b that yield reductions of grazed winter wheat crops are primarily due to green tissue removal, reduced light interception and photosynthesis, rather than to a reduction in water or nutrient acquisition by roots.…”
Section: Physiological and Mechanistic Understanding Of Grazing Effecmentioning
confidence: 99%